Pengaruh Struktur Kepemilikan Dan Karaktresistik Perusahaan Terhadap Tax Avoidance - Waode Dwi Wulandari; Salim Assoba; Lia Uzliawati (Politeknik Ganesha Medan, 2023)
Many companies can carry out many strategies in carrying out tax planning. One of the tax planning strategies is tax avoidance, namely how to reduce taxes legally. Tax avoidance practices usually take advantage of weaknesses in tax law and do not violate tax law. Besides doing tax evasion by using tax law loopholes (loopholes). This tax avoidance strategy (tax avoidance) is a method that is permitted by law but the strategy implemented by this company still receives state revenue, Related to this tax avoidance in Indonesia in 2005 there were 750 foreign investment companies that suspected of committing tax evasion by reporting losses in 5 consecutive years and not paying taxes. The objectives of the research were to examine and analyze the influence of stock ownership majority, leverage, capital intensity, and profitability toward tax avoidance. In this research, tax avoidance produced by Current Effective Tax Ratio (CETR). The population and sample of this research is the mining companies that listing in the Indonesian Stock Exchange (BEI) at the period 2010-2014. The sample of this research was 8 mining companies with 40 data observation. The method used in this research was multiple linear regression models. In this research, the data was processed by using IBM software Statistical Package for Social Science (SPSS) version 22. The results of this research indicated that leverage and profitability did not give significant effect toward tax avoidance. Meanwhile, majority stock ownership and capital intensity was gave negative effect toward tax avoidance.